A Dyadic Approach to Understanding Associations Between Job Stress, Marital Quality, and Dyadic Coping for Dual-Career Couples in Iran - Fallahchai, Reza; Fallahi, Maryam; Randall, Ashley K. (Frontiers in Psychology, 2019)
In Iran, dual-career couples face many stressors due to their demands of balancing work and family. Moreover, the experience of this stress can negatively affect partners’ martial quality. Recent studies have shown the positive impact of dyadic coping on well-being; however, a majority of this research has been conducted with Western cultures. As such, there is a dearth of literature on understanding how supportive and common dyadic coping may have a positive association with work-family stress for couples in Iran. Using a sample of 206 heterosexual dual-career couples from Iran, this study examines the associations between job stress and marital quality, and possible moderating effects of common and perceived partner supportive dyadic coping. As predicted, job stress was negatively associated with marital quality, and this association with further moderated by gender, such that women who experienced greater job stress also reported lower marital quality. Additionally, dyadic coping moderated the association between job stress and marital quality. Common dyadic coping attenuated the negative association between job stress and marital quality. The findings shed light on the possible beneficial effects of teaching supportive and common dyadic coping techniques to dual-career couples in Iran.